Managing unproven technology - George K. Chacko, Ph.D. (Thomson Learning, 2006)
Here for the first time, internationally-renowned systems scientist and practitioner, George K. Chacko, Ph.D., who was Manager of Operations Research Department of Hughes Semiconductor Division, and Senior Staff Scientist with TRW Systems before joining University of Southern California as Professor of Systems Management in 1970, develops an original 12-step Management of Technology Protocol (MOTEP) and applies it to 51 Applications. They range from Du Pont's failure in Nylon to Single Online Trade Exchange for Auto Parts Procurement by GM, Ford, Daimler-Chrysler and Renault-Nissan; and from R&D of Unborn Radar (UK) and Commitment to Lunar Landing (USA) to IBM-AT&T Wireless Business Service, and AOL-Microsoft Concomitant Coalitions, in which the same parties compete and co-operate simultaneously